Market based control of linear structural systems. - Lynch, Jerome Peter
To limit the response of structures during external disturbances such as strong winds or large seismic events, structural control systems can be used. In the structural engineering field, attention has been shifted from active control to semi active control systems. Unlike active control system devices, semi active devices are compact, have efficient power consumption characteristics and are less expensive. As a result, an environment of a large number of actuators and sensors will result, rendering a complex large scale dynamic system. Such a system is best controlled by a decentralized approach such as market based control (MBC). In MBC, the system is modelled as a market place of buyers and sellers that leads to an efficient allocation of control power. The resulting MBC solution is shown to be locally Pareto optimal. This novel control approach is applied to three linear structural systems ranging from a one storey structure to a 20 storey structure, all controlled by semi active hydraulic dampers. It is shown that MBC is competitive in the reduction of structural responses during large seismic loadings as compared to the centralized control approach of the linear quadratic regulation controller.
Keywords: Market based control (MBC).; Semi active control; Active control; Decentralized structural control; Smart structures; Linear quadratic regulation (LQR).